Theoretical examination of long-range energy propagation in nano-engineered light-harvesting antenna arrays - Yang, Guangcan (2012)
Excitation energy transport in a biomimetic molecular nanoarray constructed from LH2 antenna complexes is investigated by a master equation approach including the effect of coherent hopping. Calculated stationary and transient fluorescence signals upon incidence of a diffraction-limited light pulse are compared with measurements. Energy transport was established from the influence of active energy-guiding layers on the observed fluorescence emission. Energy migration occurs as a result of efficient coupling between many hundreds of LH2 complexes. We obtain an analytical expression of stationary fluorescence distribution solving the master equations of the system. The time-dependent fluorescence intensity is derived using the same formalism. The numerical results show a reasonable consistency with the experimental result in the engineered nanoarray of LH2 complexes. In addition, our results show that quantum coherence mechanism is necessary to explain the long distance energy transport. These results demonstrate the potential for long-range energy propagation in hybrid systems composed of natural light-harvesting antenna molecules from photosynthetic organisms.